War by numbers understanding conventional combat - Lawrence, Christopher A. (Potomac Books, an imprint of the University of Nebraska Press, 2017)
Assesses the nature of conventional warfare through the analysis of historical combat. Christopher A. Lawrence establishes what we know about conventional combat and why we know it. By demonstrating the impact a variety of factors have on combat he moves such analysis beyond the work of Carl von Clausewitz and into modern data and interpretation